2000
DOI: 10.1177/089686080002000206
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of Immediate Full-Volume Exchange One Year after Peritoneal Catheter Implantation for CAPD

Abstract: Objective To evaluate actual risk of complications and 1-year catheter survival of immediate full-volume 2000-mL dialysate exchange after peritoneal catheter implantation. Design and Setting A prospective randomized comparative study in a university hospital kidney center. Patients The study included 59 end-stage renal disease patients entering into a continuous ambulatory peritoneal dialysis program between January 1996 and December 1997. Interventions In group 1 ( n = 21), exchange volume was gradually incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
36
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 9 publications
2
36
0
Order By: Relevance
“…In this study, the start volume of dialysate was 500 ml and the volume was gradually increased to 1500 ml. On the other hand, Song et al showed that immediate full volume dialysate exchange did not cause leakage and catheter loss after percutaneous insertion [17]. These results of catheter-related infection and of technique failure are consistent with our results.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, the start volume of dialysate was 500 ml and the volume was gradually increased to 1500 ml. On the other hand, Song et al showed that immediate full volume dialysate exchange did not cause leakage and catheter loss after percutaneous insertion [17]. These results of catheter-related infection and of technique failure are consistent with our results.…”
Section: Discussionsupporting
confidence: 92%
“…The most frequent problem preventing immediate initiation of PD with most insertion techniques is the risk for early leakage at the peritoneal entry zone. In some recent reports, leakage is present in 5–20% of patients (9–12), while other studies report leakage in only about 1% of patients (5,6,13,14). Use of a peritoneoscopic insertion technique was, in some studies, associated with more frequent leaks (15,16), while in others more favorable data were reported (12,17).…”
mentioning
confidence: 91%
“…Such practice of PD initiation, i.e., urgent-start PD, has recently gained resurgent momentum as an option of dialysis treatment especially for the late-referred CKD patients [ 5 7 ]. Indeed, there is accumulating evidence indicates that urgent-starters of PD exhibit a similar short-term patient survival and technique failure as the traditionally planned counterpart [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%